Assessing the relationship between menstrual products and reproductive and urogenital tract infections (RUTIs): A systematic review evaluating the evidence and recommendations for future research - Ana Krause; Gregory K. Zane; Andrea C. Rivas-Nieto; Abigail Mulugeta; Md. Rezaul Hossain; R. Scott McClelland; Jairam R. Lingappa; Stephen E. Hawes (PLoS ONE, 2025)
Background Concerns regarding the effects of non-tampon menstrual products on reproductive and urogenital health, particularly the risk of infections, is an area of ongoing investigation. We conducted an updated systematic review to assess the methodological quality of current evidence assessing associations between menstrual product use and reproductive and urogenital tract infections (RUTIs), and offer recommendations for future research. Methods Three databases (PubMed, Web of Science, United States Food and Drug Administration Manufacturer User Facility Device Experience) were searched for relevant published studies or product safety reports up to October 13, 2024. We included studies on menstruators of any age and geography assessing for any reusable/disposable menstrual pads, menstrual cups, or homemade alternatives worn only for menstrual absorbency compared to other menstrual products or no product use, with outcomes centered on RUTIs. Protocols, reviews, and studies assessing only tampons or non-menstrual absorbents were excluded. Results were evaluated and synthesized using tabular methods according to measures of association, and assessed across four criteria categories 1) product definition, 2) comparator definition, 3) outcome definition, and 4) confounder consideration. Results Thirty-one studies were included in this review. Most studies clearly defined outcomes and considered necessary confounders. In contrast, studies with well-defined products (6.5%) and comparator products (9.7%) were uncommon. Just 3.2% and 9.7% of studies fully defined products and comparators, respectively. Ten studies (32.2%) reported some data on four or more confounders, and seventeen (54.8%) defined their infectious outcomes and included laboratory confirmation. A meta-analysis was not possible due to data heterogeneity across product, comparator, and outcome definitions. Overall, associations between menstrual products and RUTIs are inconclusive. Conclusion Future studies should 1) clearly define product and comparator type, material, frequency of change, and washing, drying, and storage practices for reusable products, 2) prioritize laboratory or clinician-confirmed outcomes over self-reported symptoms, and 3) adjust for relevant confounders.